Innovative Material Can Mimic Coral and Boulder Reefs Properties - Margheritini, Lucia; Møldrup, Per; Jensen, Rasmus Lund; Frandsen, Kirstine Meyer; Antonov, Yovko Ivanov; Kawamoto, Ken; de Jonge, Lis Wollesen; Vaccarella, Raffaele; Bjørgård, Trine Larsen; Simonsen, Morten Enggrob (Frontiers in Marine Science, 2021)
Low-Voltage Mineral Deposition technology (LVMD), widely known as Biorock, has previously been suggested as support for coral reef restoration, as hypothesized high porosity, wide pore-size distribution and connectivity, and good strength properties may facilitate biological functions (for example larvae settlement) and durability. In this technology, very low voltage induces an electrical current that initiates precipitation and accretion of hard minerals (aragonite and calcite) on a metal in seawater. This technology has been discussed mainly for its biological value, while this paper wants to highlight also its engineering value as artificial reef material. Indeed, some of the properties that makes it valuable in one domain are also supporting its use in the other. Because the metal on which the precipitation takes place can be of any shape and size, so can the artificial reef and its mechanical strength characteristics are above the ones of corals and similar to concrete, indicating adequate durability. Coral and boulder reefs suffering from degradation have severe implications on biodiversity, protection from flooding, and cultural value and therefore understanding how to persevere and re-establish these ecosystems is central for sustainable intervention in the marine environment. By comparing chemical-physical characteristics of Coral Porites Exoskeleton (CPE), one typical reef building coral type, LVMD and High-Voltage Mineral Deposition (HVMD), we show that they possess highly similar properties including chemical composition, density, total porosity, pore-size distribution, physical and chemical heterogeneity, total and external surface areas, and comparable mechanical strength.